A recipe for an unpredictable random number generator - Garcıa-Nustes, M.A.; Trujillo, L.; Gonzalez, J.A. (Condensed Matter Physics, 2006)
In this work we present a model for computing the random processes in digital computers which solves the problem of periodic sequences and hidden errors produced by correlations. We show that systems with noninvertible non-linearities can produce unpredictable sequences of independent random numbers. We illustrate our results with some numerical calculations related to random walks simulations.